Dinamika Keluarga Muslim di Era Digital: Analisis Implikasi Media Sosial terhadap Keharmonisan Keluarga Perspektif Psikologi Keluarga Islam - Noni Kensiwi; Fiqi Restu Subekti (PT Taskuliah Edukasi Indonesia, 2026)
This study aims to analyze the implications of social media for the dynamics of Muslim families from the perspective of Ahmad Mubarak al-Kandari’s Islamic Family Psychology. Social media has become an integral part of modern family life and significantly influences communication patterns, parenting practices, and household harmony. This study employs a qualitative approach using a library research method. Data were obtained from online news reports as the primary source and supported by relevant academic literature. The data were analyzed through documentation techniques, content analysis, and thematic analysis to identify the influence of social media on family functions, interactional meanings, developmental stages, social learning processes, and the psychological dynamics of family members. The findings reveal that social media has ambivalent implications. On the one hand, social media strengthens communication, expands access to religious education, reinforces collective identity, and creates economic opportunities for families. On the other hand, it may reduce the quality of face-to-face interaction, trigger marital conflict, weaken parental authority, and contribute to psychological problems among children and adolescents. Therefore, the management of social media based on Islamic values and an understanding of family psychology is essential to maintain the functionality and resilience of Muslim families in the digital era. [Penelitian ini bertujuan menganalisis implikasi media sosial terhadap dinamika keluarga Muslim dalam perspektif Psikologi Keluarga Islam Ahmad Mubarak al-Kandari. Media sosial telah menjadi bagian penting dalam kehidupan keluarga modern dan memengaruhi komunikasi, pengasuhan, serta keharmonisan rumah tangga. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka. Data diperoleh dari berita online sebagai sumber utama yang dipadukan dengan literatur akademik relevan. Analisis dilakukan melalui teknik dokumentasi, analisis isi, dan analisis tematik untuk memetakan pengaruh media sosial terhadap fungsi keluarga, makna interaksi, tahapan perkembangan, pembelajaran sosial, dan dinamika psikologis anggota keluarga. Hasil penelitian menunjukkan bahwa media sosial memiliki dampak ambivalen. Di satu sisi, media sosial dapat memperkuat komunikasi, memperluas akses edukasi keagamaan, membangun identitas kolektif, serta membuka peluang ekonomi keluarga. Namun di sisi lain, media sosial juga berpotensi menurunkan kualitas interaksi tatap muka, memicu konflik pasangan, menggeser otoritas pengasuhan, serta menimbulkan masalah psikologis pada anak dan remaja. Oleh karena itu, pengelolaan media sosial yang berlandaskan nilai-nilai Islam dan pemahaman psikologi keluarga menjadi kunci untuk menjaga keberfungsian dan ketahanan keluarga Muslim di era digital].